A study on postpartum symptoms and their related factors in Korea - Ji Yeon Lee; Jong Yun Hwang (Elsevier, 2015)
Objective: This study was aimed to identify the physical and mental state of women after delivery, to investigate the factors that influence those, and to examine the effects of postpartum care performance, which is traditionally believed to be appropriate care in Korea, on women's physical and mental status. Materials and Methods: A total of 148 women who visited our hospital for postpartum check-up on the 2nd week or 6th week after delivery were selected. We researched postpartum care methods using a questionnaire and had the women self-evaluate their postpartum symptoms. Depression was evaluated using the Beck Depression Inventory. Results: The average points of the 27 postpartum symptoms was 2.70 points (from 1 = very good to 5 = very bad). Seventy-two women had depression. Factors related to postpartum symptoms and depression were smoking before pregnancy, low marital satisfaction, bad mood during and after pregnancy, lack of support from husbands, and bad quality of sleep during puerperium. Treating the joints of hands carefully when milking breasts, and avoiding squatting down, demonstrated a negative correlation with the average points of postpartum symptoms. Multivariate linear regression analysis showed that mood during puerperium and Beck Depression Inventory points were significant factors related to the average points of postpartum symptoms and that the degree of support from husbands and mood during pregnancy were statistically related with depression. Conclusion: Many women complained of postpartum discomfort. Although, while some postpartum care methods which are traditionally believed to be appropriate care in Korea can be helpful to women's recovery, most of them are not. We confirmed that physical symptoms and depression are closely related to each other.